The Minutes of the Senate Academicus of the State of Georgia, 1799-1842, at 86 (1810) - (:unkn) unknown (General Publisher, 1842)
Banning students from keeping any gun, pistol, Dagger, Dirk sword cane or any other offensive weapon on campus. Also banned students from possessing them out of the college in any case whatsoever.
--
Keywords: SENSITIVE PLACES